Kombinasi Pemberian Terapi Okupasi Pasien Pasca Stroke: A Scoping Review - Fadhilah, Adinda; Pahria, Tuti; Nursiswati, Nursiswati (Universitas Malahayati, 2025)
ABSTRACT Occupational therapy for stroke patients is an important phenomenon in rehabilitation, which emphasizes the restoration of the patient's functional and social abilities through a structured and evidence-based therapeutic approach. Occupational therapy for stroke patients aims to restore their abilities in daily activities and improve their quality of life through holistic therapeutic interventions. The aim of this research is to map the results of literature findings regarding the effectiveness of occupational therapy interventions for stroke patients in improving independence in daily activities and improving their overall quality of life. The search databases for this study were PubMed, ScienceDirect, and Google Scholar. Article identification was carried out based on the criteria of year of publication (2014-2024), Randomized Control Trials (RCTs), Multicenter, Prospective, Qualitative study, and Longitodinal study, English and Indonesian, and full text. Using the PRISMA Flow Chart diagram, data extraction was carried out by including keywords (in English):